The peasantry of the Ukrainian SSR in the 1920s: trends of social and political behavior - Fareniy, Igor (Ukrainian Peasant, 2025)
Abstract. The purpose of the study is to find out the political potential of the peasantry and the results of their amateur political behaviour in the 1920s. Methodology. The study was conducted from the perspective of the concept of the peasant revolution, which aims to show the political consequences of the peasant revolutionary struggle. The concept of ‘socio-political behaviour’ is considered as a reaction to political events and independent social actions in the sphere of political life, which are conditioned by political culture and social conditions of life, aimed at protecting their interests. Scientific novelty. The political life of the peasantry of the Ukrainian SSR in the 1920s is examined from the standpoint of the concept of the peasant revolution. Conclusions. In the socio-political behaviour of the Ukrainian peasantry of the 1920s, various trends were manifested: readiness for armed methods of solving social issues and peaceful ways of influencing political life. The violent form of political behaviour was manifested until the mid-1920s and was suspended as a result of the satisfaction of the peasantry’s land claims, the abolition of product layouts and physical and moral fatigue from the war. At the end of the decade, it began to return to the practice of political behaviour in connection with the volume of state grain procurement. During the 1920s, the peasantry demonstrated the ability to develop peaceful political self-organisation on the basis of traditional communal orders and to establish public associations to protect their social interests, and to master the work of official authorities – in village councils. The social and political activity of the peasantry was driven by dissatisfaction with their situation, the low level of capacity of the state authorities and their favouritism towards the urban population. The peasantry tried to develop a regime of power based on community traditions in the form of land communities – organisations for the distribution of land. Legislation on land communities was one of the compromises made by the peasant revolution with the Bolshevik government. However, the land communities did not become a full-fledged government, and their activities beyond their officially defined powers were gradually suspended. The Soviet form of government was imposed on the peasantry, but the peasantry took over the work of village councils. As a result of obstacles to the creation of a peasant political party, the peasantry was unable to effectively use the capabilities of the official authorities. The peasantry faced the socio-economic and political transformations of the turn of the 1920s and 1930s in a state of destruction of traditional communal orders, lack of a political force ready to represent and protect peasant social interests, and insufficient control of official authorities. This resulted in the inability to resist ‘collectivisation’ and grain procurement, which caused the reversal of the peasant revolution and the Holodomor.